Myocardial perfusion SPECT with dipyridamole stress test in cardiac syndrome X - Czepczyński, R.; Smolarek, I.; Rogacka, D.; Kazmiercźak, M.; Wysocki, H.; Sowiński, J. (Nuklearmedizin - NuclearMedicine, 2006)
Cardiac syndrome X defines patients with typical anginal chest pain, a positive exercise ECG stress test and angiographically normal coronary arteries. Aim of this study was to evaluate the role of myocardial perfusion SPECT with dipyridamole stress in the diagnosis of cardiac syndrome X. Patients, methods: 68 patients with syndrome X aged 32 to 60 years were subjected to myocardial imaging using 99mTc-MIBI according to the two-days protocol: at rest and after dipyridamole infusion. Semiquantitative evaluation of the images was based on the assessment of 99mTc-MIBI uptake in 17 myocardial segments using a 5-points scale (0 point – normal uptake, 4 points – no uptake). Scores obtained in each segment were summed up, constituting the summed rest score (SRS) and summed stress score (SSS). Results: Mean SRS was 7.9 ± 4.8 and mean SSS was 7.2 ± 4.4 (non-significant difference). Individual comparison of SRS and SSS values revealed three patterns of scintigraphic images: 1) in 25 patients (36.8%), a paradoxical improvement of perfusion at stress images was found, 2) in 23 patients (33.8%), the myocardial perfusion deteriorated after dipyridamole, 3) in 20 patients (29.4%), no significant change of the myocardial perfusion between rest and stress images occurred. Conclusions: In cardiac syndrome X, myocardial SPECT with dipyridamole stress shows different patterns of myocardial perfusion that reflects heterogeneity of this pathology.
Keywords: Cardiac syndrome X; 99mTc-Sestamibi; SPECT; dipyridamole; coronary angiography